2013
DOI: 10.1371/journal.pone.0083579
|View full text |Cite
|
Sign up to set email alerts
|

Tat Peptide-Mediated Soluble Expression of the Membrane Protein LSECtin-CRD in Escherichia coli

Abstract: The human liver and lymph node sinusoidal endothelial cell C-type lectin (hLSECtin), a type II integral membrane protein, containing a Ca2+-dependent carbohydrate recognition domain (CRD), has a well-established biological activity, yet its three-dimensional structure is unknown due to low expression yields and aggregation into inclusion bodies. Previous study has demonstrated that the HIV-1 virus-encoded Tat peptide (‘YGRKKRRQRRR’) can increase the yields and the solubility of heterologous proteins. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Preliminary experimental data showed that Tat-LSECTin was mainly expressed in the cell lysate supernatant, in the form of inclusion bodies, and that the Tat-LSECTin protein expression yield was significantly higher than that of LSECTin alone. 41 These results support the idea that Tat core peptides also promote high yield and soluble expression of membrane proteins containing disulfide bonds, and indicate that addition of a Tat tag could promote high yield and soluble expression of proteins in E. coli regardless of whether they were membrane proteins or disulfide bond-rich proteins, thereby providing a novel tool for heterologous protein expression in E. coli .…”
Section: Discussionsupporting
confidence: 75%
“…Preliminary experimental data showed that Tat-LSECTin was mainly expressed in the cell lysate supernatant, in the form of inclusion bodies, and that the Tat-LSECTin protein expression yield was significantly higher than that of LSECTin alone. 41 These results support the idea that Tat core peptides also promote high yield and soluble expression of membrane proteins containing disulfide bonds, and indicate that addition of a Tat tag could promote high yield and soluble expression of proteins in E. coli regardless of whether they were membrane proteins or disulfide bond-rich proteins, thereby providing a novel tool for heterologous protein expression in E. coli .…”
Section: Discussionsupporting
confidence: 75%
“…These transmembrane helix structures may cause difficulties for our protein expression in vitro. However, producing a prokaryotic membrane protein in the simple, flexible, and inexpensive E. coli system has already proven successful in many cases [ 55 , 56 , 57 ]. Unfortunately, the yield and quality of membrane proteins, especially eukaryotic ones, are often insufficient for structural and functional studies in E. coli [ 58 ].…”
Section: Discussionmentioning
confidence: 99%